Penerapan IPTEKS pada usaha Handycraft Ketak berorientasi Ekspor di desa Karang Bayan Kecamatan Lingsar Kabupaten Lombok Barat - Triadi, A.A.A.; Nuarsa, M.; Bisma, DG. (Universitas Mataram, 2017)
Products Woven or ketak is a handicraft product produced by the ‘artisans’ community in the village of Karang Bayan West Lombok with raw materials from plants ketak. In the process it takes the necessary skills to weave and combine woven ketak with other natural products such as wood, pottery, coconut shell or bone. The marketing of wicker web products has penetrated the export market, especially the Japanese market. Problems experienced by industrial partners or the artisan’s community is the transfer of design from businessmen to crafters (door to door), drying process during the rainy season and business management. Designs are sometimes made by the buyer and sent to the entrepreneur via email. The solving problem that is faced by the producents is the important thing to be done, by approaching the centralized design transfer training (in one place that is done in the partner house). The next one, making a mechanical dryer with two heat sources located beside left and lower right and LPG-fueled (clean, practical, economical and environmentally friendly). Next step, by providing business management assistance (finance and marketing).